Formulasi Ubi Jalar Orange (Ipomoea batatas L.) dan Tepung Ikan Tuna (Thunnus sp) Dalam Pembuatan Mie Kering - Holimombo, Jaetuna; Palijama, Syane; Augustyn, Gelora H (Jurnal Agrosilvopasture-Tech, 2023)
The purpose of this study was to determine the formulation between orange Sweet Potato and tuna fish flour in the manufacture of dried noodles. This study was designed using a non-factorial complete randomized design (RAL) with orange sweet potato formulation and tuna fish meal with four levels of treatment (70%:30%, 75%:25%, 80%:20% and 85%:15%) with three repetitions. The data observed were chemical tests (moisture content, ash content, fat content, protein content, carbohydrate content and fiber content). While the physical test (water absorption, cooking time and elasticity). And organoleptic (hedonic test and hedonic quality). The results of the study with the formulation of sweet potato orange: tuna fish meal (75%:25%) is the best treatment in the manufacture of dried noodles with chemical test results are water content of 10,91%, ash content of 3,79%, fat content of 1,09%, protein content of 24,93%, carbohydrate content of 59,17% and fiber content of 3,64%. While the physical test of water absorption is 232,63%, cooking time is 320 seconds and elasticity is 15,07%. Based on the organoleptic results test, dried noodles with orange sweet potato formulation and tuna fish flour (80%:20%) were the best treatment in terms of hedonic and hedonic quality respectively including color before boiling 2,91 (rather liked)/after boiling 3,0 (likes) and 2,83 (slightly orange), taste 3,0 (likes) and 2,58 (slightly tastes of fish), aroma 3,12 (likes) and 2,75 (rather smells of fish), texture 2,91 (rather like) and 2,83 (rather chewy), overall 2,95 (rather like).